Distraction/Suppression and Distress Endurance diminish the extent to which generalized conditioned fear is associated with maladaptive behavioral avoidance. (September 2017) - Hunt, Christopher; Cooper, Samuel E.; Hartnell, Melissa P.; Lissek, Shmuel
Abstract: A central conditioning correlate of clinical anxiety is the over-generalization of Pavlovian fear to safe stimuli resembling conditioned danger cues (CS+). Though much of the pathogenic influence of such generalization may lie in the unnecessary behavioral avoidance it evokes, few studies have examined maladaptive avoidance associated with Pavlovian generalization. Lab-based assessments of this process, here referred to as instrumental avoidance from Pavlovian generalization (IAP-G), have recently begun. The current study represents a next step in this line of work by examining personality factors that may reduce maladaptive IAP-G. This is a clinically relevant effort, as such traits may reflect resilience factors, with high levels reducing the likelihood of maladaptive generalized avoidance following Pavlovian generalization. Here we focus on the effects of Distraction/Suppression (DS) and Distress Endurance (DE) on IAP-G. Results indicate that both DS and DE moderate IAP-G by weakening relations between Pavlovian generalization of fear-potentiated startle and maladaptive generalized avoidance. Further, moderating effects of DS were most pronounced for more ambiguous cues of threat (i.e., stimuli moderately resembling CS+), while moderating effects of DE were most pronounced for more certain cues of threat (i.e., stimuli highly resembling CS+, as well as the CS + itself). Results implicate DS and DE as protective factors against the maladaptive behavioral consequences of Pavlovian generalization, and further indicate that the protective influence of these traits may depend on the ambiguity of the threat at hand. Highlights: Generalization of Pavlovian fear results in maladaptive avoidance. Distraction/Suppression (DS) & Distress Endurance (DE) weaken relations between generalized fear and maladaptive avoidance. Moderation of relations between conditioned fear and avoidance by DS were most pronounced for more ambiguous cues of threat. Moderation of relations between conditioned fear and avoidance by DE were most pronounced for more certain cues of threat. All effects of DS and DE on relations between Pavlovian fear and avoidance remain after controlling for trait anxiety.